Educación financiera y gestión de las finanzas personales de los clientes de Caja Piura, Iquitos 2020 - Luque Rios, Doorlita (2021)
The general objective of this research was to determine the relationship between financial education and the management of personal finances of Caja Piura clients, Iquitos 2020; Given this, the type of research was applied, correlational level and non-experimental design, for which a sample of 327 clients was taken from a population of 2,856; Subsequently using the survey as a technique and the questionnaire as a data collection instrument, to finally conclude that financial education is significantly related to the management of clients' personal finances, which is corroborated by the Rho correlation coefficient equal to at 0.829. Joint goal setting is significantly related to the management of clients' personal finances, which is corroborated by the Rho correlation coefficient equal to 0.822. Budget management is significantly related to the management of clients' personal finances, which is corroborated by the Rho correlation coefficient equal to 0.830 and contrasted with a significance (bilateral) of 0.000. Knowledge of savings products is significantly related to the management of clients' personal finances, which is corroborated by the Rho correlation coefficient equal to 0.809. The use of credits is significantly related to the management of clients' personal finances, which is corroborated by the Rho correlation coefficient equal to 0.821. The means of payment and money transfer are significantly related to the management of the clients' personal finances, which is corroborated by the Rho correlation coefficient equal to 0.822. Relations with financial institutions are significantly related to the management of clients' personal finances, which is corroborated by the Rho correlation coefficient equal to 0.824.